2003
DOI: 10.1126/science.1080106
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Lysosomal Function During Dendritic Cell Maturation

Abstract: In response to a variety of stimuli, dendritic cells (DCs) transform from immature cells specialized for antigen capture into mature cells specialized for T cell stimulation. During maturation, the DCs acquire an enhanced capacity to form and accumulate peptide-MHC (major histocompatibility complex) class II complexes. Here we show that a key mechanism responsible for this alteration was the generalized activation of lysosomal function. In immature DCs, internalized antigens were slowly degraded and inefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
549
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(575 citation statements)
references
References 39 publications
25
549
1
Order By: Relevance
“…29,30 In conclusion, the above arguments collectively convince about the strength of data. However, as in the case of an association being (7) 13/23 (10) 1234 Â 1234 a (9) 13/24 (11) a…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 In conclusion, the above arguments collectively convince about the strength of data. However, as in the case of an association being (7) 13/23 (10) 1234 Â 1234 a (9) 13/24 (11) a…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] The study was extended to six SNPs (rs36027301, rs4147779, rs2471829, rs4147778, rs4147780 and rs2075609), which are not found in patients affected with osteopetrosis. 4 The corresponding alleles were therefore expected to be present in the population at a reasonable frequency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the mechanism of Ag presentation in mDCs delivered by R8-Lip, the mature cells were incubated with lactacystin (a specific proteasome inhibitor) or leupeptin (an endosomal proteases inhibitor). Only lactacystin showed the markedly inhibition of pMHC presentation ( reported that the induction of maturation lowers endosomal/ lysosomal pH by ~1 pH unit, from pH 5.5 to pH 4.5 [34,35]. The acidified endosomes of mDCs may be preferable for R8-Lip-OVA escape from endosomal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…The maturation of dendritic cells is associated with a substantial increase in V-ATPase activity, regulated mainly by recruitment of inactive subunits. 26 Interestingly, a recent study has demonstrated that expression of the d2-subunit of V-ATPase is restricted to subsets of dendritic cells, suggesting that alterations in subunit expression may not only regulate enzyme activity but also influence immune cell differentiation and function. 27 The G2 isoform mRNA has been detected in a number of tissues with the highest expression seen in the nervous system.…”
Section: Discussionmentioning
confidence: 99%